2003
DOI: 10.1128/aem.69.4.2073-2079.2003
|View full text |Cite
|
Sign up to set email alerts
|

Exopolysaccharide and Kestose Production by Lactobacillus sanfranciscensis LTH2590

Abstract: The effect was investigated of sucrose concentration on sucrose metabolism and on the formation of exopolysaccharide (EPS) by Lactobacillus sanfranciscensis LTH2590 in pH-controlled fermentations with sucrose concentrations ranging from 20 to 160 g liter ؊1 . The EPS production increased and the relative sucrose hydrolysis activity decreased by increasing the sucrose concentration in the medium. The carbon recovery decreased from 95% at a sucrose concentration of 30 g liter ؊1 to 58% at a sucrose concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
62
0
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(69 citation statements)
references
References 36 publications
4
62
0
3
Order By: Relevance
“…The ability of levansucrase enzymes to synthesize b(2R1)-as well as b(2R6)-linked FOSs has been reported elsewhere (Euzenat et al, 2005;Támbara et al, 1999;Korakli et al, 2003). Lb.…”
Section: Ftf Synthesis Of Inulin-and Levan-like Fossmentioning
confidence: 99%
See 1 more Smart Citation
“…The ability of levansucrase enzymes to synthesize b(2R1)-as well as b(2R6)-linked FOSs has been reported elsewhere (Euzenat et al, 2005;Támbara et al, 1999;Korakli et al, 2003). Lb.…”
Section: Ftf Synthesis Of Inulin-and Levan-like Fossmentioning
confidence: 99%
“…This suggests that the growing polymer chain remains bound to the enzyme, and that fructan-chain elongation proceeds via a processive type of reaction. In contrast, the enzymes of Gluconacetobacter diazotrophicus, Zymomonas mobilis and Lactobacillus sanfranciscensis have been found to synthesize mainly short fructooligosaccharides (FOSs; kestose and nystose) from sucrose (Doelle et al, 1993;Hernández et al, 1995;Korakli et al, 2001Korakli et al, , 2003; thus, these enzymes may employ a nonprocessive type of reaction, involving release of the fructan chain after (virtually) each fructosyl transfer. The available three-dimensional structures of the B. subtilis SacB levansucrase, which synthesizes mainly large polymers, and the FOS-synthesizing levansucrase from G. diazotrophicus (Martinez-Fleites et al, 2005;Meng & Futterer, 2003), show that the active-site architecture of both levansucrase enzymes is identical (Martinez-Fleites et al, 2005;Meng & Futterer, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The highest exopolysaccharide producing isolate strain was L. plantarum (810.75 mg/L) whereas, the least exopolysaccharide producing isolate was L. crispatus (242.5 mg/L). The values obtained for EPS production and cell dry weight were comparable with data obtained in previous experiments with lactic acid bacteria species/strains (Cerning, 1990; Cerning, Bouillanne, Landon, & Desmazeaud, 1992; Korakli et al., 2003; Minervini et al., 2010; Mozzi, Savoy de Giori, Oliver, & Font de Valdez, 1996; Vogel, 2008). Other studies have also reported that some microorganisms are capable of producing and excreting over 40 g/L of EPSs under conditions of stress (Lin & Cheng‐Chien, 2007; Papinutti, 2010; Ravella et al., 2010).…”
Section: Resultsmentioning
confidence: 99%
“…The low yields EPSs production by majority of LAB species has reduced their commercial viability and limited industrial applications. Studies have showed that some LAB species have potentials to produce high yields EPSs roughly 40 g/L (Kaditzky & Vogel, 2008; Korakli, Pavlovic, Ganzle, & Vogel, 2003; Minervini et al., 2010). Industrial applications of natural polymers for various uses have increased their demand and this has led to an increased attention toward exopolysaccharides and this has re‐enforced the search for LAB strains with potentials for production of high yields EPS.…”
Section: Introductionmentioning
confidence: 99%
“…By contrast HoPS were reported to be produced in considerably larger amounts up to 40 gL -1 . 6 Leuconostoc and Lactobacillus species form HoPS in the presence of sucrose. 3 A variety of Lactobacillus reuteri strains synthesise fructans and glucans with differing molecular properties, e.g.…”
Section: Introductionmentioning
confidence: 99%